Seed germination responses to soil hydraulic conductivity and polyethylene glycol (PEG) osmotic solutions - Camacho Umaña, Manuel Ernesto (2021)
Aims Seed germination is one of the most important processes in plant biology and ecology because it determines the timing and magnitude of seedling emergence events every growing season influencing community dynamics. Our aim was to determine whether polyethylene glycol (PEG) solutions simulate soil water potential accurately and recreate germination responses to soil water availability. Methods In this study, we compared seed germination of four plant species in PEG and four soils with different textures under six water potentials under controlled laboratory conditions. Results Total seed germination for all species significantly differed between soil and PEG under the same water potentials, as well as among soil water potentials for each of PEG and soil materials. Due to the inconsistent total germination associated with soil water potential, we evaluated unsaturated soil hydraulic conductivity (Kh) as a predictor of germination. The germination of all species followed the same response to Kh. Germination rate (GR50) was more directly related to water potential than total germination, but Kh provided a more robust description of GR50 across species and soils than PEG-osmotic potentials. Conclusions Our findings showed that Kh is a more informative variable to predict both total seed germination and germination rate in soil, and caution must be used when considering results obtained using PEG solutions to infer germination behavior under field conditions.